Domestic Violence against Women : (A Case Study of Nepalgunj Sub-Metropolitan -12) - Gautam, Jentil (Academia Research Journal, 2023)
In Nepal, a tiny federal, inclusive secular state with a wide range of cultural traditions, women are treated as second-class citizens and are routinely denied their basic human right to be free from abuse. The benefits and authority bestowed by the complex social structures, which are dominated by men, impose values, practices, morals, habits, and beliefs that compel women to endure men's aggression. Domestic violence is any violence committed by a large group against women who are involved in personal relationships. In Nepalese society, violence against women is still a very severe and taboo issue. The primary goals of the study was to sketch out the socio-demographic profile of Nepalgunj Ward 12 and to pinpoint the root causes of domestic violence against women as well as to gather suggestions for its prevention and eradication. The households were chosen using a planned sample technique. Descriptive statistics were employed in the analysis of the results, including frequency, percentage, and graph. Physical and psychological abuse accounts for 7.5% and 92.5%, respectively, of all domestic violence cases. Traditional violence as it has historically been connected was not reported by the respondents. Violence exists nowhere in the research location, hence there is no dowry-related violence there. The majority of the abuses, or 47.5%, include aggressive acts committed while intoxicated. The majority of abusers engage in violent behavior on weekends. A small percentage of the women beat their partners when they were expecting, and a few of them required medical attention as a result. The study found that the most effective methods for reducing domestic violence are counseling, income production initiatives, adult literacy and awareness training, and the prohibition of alcohol, gambling, and marijuana.